LOCAL KNOWLEDGE OF ADAPTIVE STRATEGIES AGAINST MALARIA ENDEMICITY IN THE OKAVANGO DELTA, BOTSWANA - Maphane, Dirontsho; Ngwenya, Ntombi Barbara; Kolawole, Oluwatoyin Dare; Motsholapheko, Moseki Ronald; Pagiwa, Vincent (African Journal of Infectious Diseases (AJID), 2022)
Background: An increasing recognition of the need to eliminate malaria infection globally and particularly in Africa where more than 90% of the cases originate, should enhance community awareness and participation in the same. The perennial freshwater of Okavango Delta located in northern Botswana, which is a source of rural livelihoods and a suitable habitat for the malaria-causing mosquito, and where malaria is endemic provides a suitable environment for the study.Therefore,local households’ adaptive strategies against malaria transmission in the Okavango Delta were investigated. Materials and Methods: The data used in this paper is a subset or retrospective cohort of 79 households that reported malaria cases/incidences during the first community level household survey conducted from October-November 2015 on 355 households in Shakawe and Ngarange. The households were selected through stratified random sampling in the two study villages. The retrospective cohort household survey was conducted from 7-19 August 2016, in the two study sites. Data were collected through socio-economic survey, key informants’ interviews and focus group discussions. Results: The results obtained indicate that most cohort households embraced several adaptive strategies against malaria transmission. These included, inter alia, knowledge capacity building through attendance of health information and education workshops(69%), modifications of houses structures(49.4%), timing of activities and restricting movement at certain times of the day(43%). Discussion:Although most of the stated adaptive strategies such as house screening were not exclusively aimed towards malaria prevention and adaptation, they nonetheless had postive spill over effect that could be a catalyst for eliminating malaria in the study area.